KARAKTERISASI PARAMETER SPESIFIK DAN PARAMETER NON SPESIFIK AKAR KUNING (Fibraurea tinctoria) - Supomo Supomo; Hayatus Sa`adah; Eka Siswanto Syamsul; Kintoko Kintoko; Hardi Astuti Witasari (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2020)
One of the secondary metabolites from yellow root (Fibraurea tinctoria) that has the potential to be developed as medicine is berberine. Alkaloid class compounds are reported to have antimicrobial, anti-diarrheal, intestinal parasite infection inhibitors, antihypertensives, anti-tumor, anti-inflammatory, hepatoprotective, antimalarial and anticancer properties. In the development of natural ingredients as medicine, it is necessary to standardize simplicia and extracts The research objective was to determine the characterization of specific and non-specific parameters of yellow root plants. This research is an experimental research. The object of research used yellow roots obtained from KDKT Samboja, Kutai Kartanegara district, East Kalimantan Province. Samples were made of simplicia which were extracted using the maceration method with 70% ethanol solvent. The results of the extraction were carried out by characterization including: macroscopic, microscopic, water content, water-soluble extract, ethanol-soluble extract, ash content, and acid-insoluble ash, then phytochemical screening was carried out. Data were analyzed using descriptive methods. The results of macroscopic characterization of yellow root simplicia powder were Liana with a length of 10-20 m, with round stems, bark grayish brown, coarse, 2-7 cm in diameter and bright yellow powder color. The simplicia powder microscopy found stone cell fragments and tracheal fragments. Characterization of simplicia powder, water content of 67.3%, ethanol soluble extract content of 6.69%, water soluble extract content of 8.05%, ash content of 7.37%, acid insoluble ash content of 0.37%. The results of the identification of the chemical compound group were positive for containing chemical compounds in the form of alkaloids, flavonoids and saponins.